Facial beauty and the late positive component of event-related potentials. - Johnston, Victor S.; Oliver-Rodriguez, Juan C. (Journal of Sex Research, 1997)
A study was conducted to examine the effects of non-average female facial features and proportions on men's behavioral and electrophysiological responses. Data were drawn from 25 males whose event-related potentials (ERPs) were recorded while viewing randomly presented male and female computer-generated faces that were subsequently rated for physical attractiveness. Results revealed that a late positive component (LPC) of the ERPs, with a parietal greater than frontal scalp distribution, was correlated with the beauty rating of female faces. In addition, modified facial proportions enhanced both the beauty rating and LPCs to female faces but not to male faces. Furthermore, other features previously revealed to enhance facial beauty systematically increased both the LPC and attractiveness ratings. It is concluded that these findings support the fertility hypothesis of female facial beauty and an affective value interpretation of the LPC.